Association between serum soluble ST2 level and right ventricle systolic function on pulmonary hypertension due to atrial septal defect - Firandi Saputra; Anggoro Budi Hartopo; Hariadi Hariawan; Dyah Wulan Anggrahini; Lucia Kris Dinarti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Pulmonary hypertension (PH) due to atrial septal defect (ASD) may cause a decline in right ventricle (RV) function. Soluble ST2 isa prognostic biomarker for left ventricle dysfunction. However, its role in RV function has not been investigated. This study aimed to investigate the association between serumsoluble ST2 with RV systolic function in patients withASD–associatedPH. This was a cross sectional study. Subjects were patients participated in the COHARD-PH registry performed in Dr. Sardjito General Hospital, Yogyakarta Indonesia. The patients with ASD and PH confirmed by right heart catheterization (RHC) were enrolled in this study. The soluble ST2 level was measured in the serum collected from pulmonary artery during RHC. Right ventricle systolic function was determined by transthoracic echocardiography using peak systolic velocity of tricuspid annulus (S’) parameter. This study was performed in 32 adults with uncorrected ASD. They predominantly females [n=29 (90.6%)] with median age of 31(22.5-44.0) years old. Mean ASD diameter was 2.69±0.53 cm. Median mean pulmonary artery pressure (mPAP) 45.0 (36.25-70.0) mmHg. Median soluble ST2 level was 23.28 ng/mL. There were no significant correlations between soluble ST2 level with S’value (r=0.071; p=0.35), with mPAP (r=0.043; p=0.815), with pulmonary vasculer resistance (PVR) (r=0.025; p=0.893) and with right ventricle (RV) diameter (r=0.200; p=0.273). Soluble ST2 level was found higher in subject with RV dysfunctionbut not statistically significant. In conclusion, serum soluble ST2 level did not associate withRV systolic function, measured by S’, in adult ASD-associated PH.